Voluntary disclosure in the context of convergence with International Accounting Standards in Brazil - Consoni, Silvia; Colauto, Romualdo Douglas (Review of Business Management, 2016)
Purpose – The purpose of this paper is to verify the influence of the convergence process to International Financial Reporting Standards on the voluntary disclosure of listed Brazilian companies. Design/methodology/approach – A voluntary disclosure metric was designed and collected from a random sample of 66 companies registered as active in BM&FBovespa during the 2005-2012 period. For the hypothesis test it was used panel data regressions with random effects. Findings – The convergence process to International Financial Reporting Standards is presented as an exogenous factor that affected positively and significantly voluntary disclosure in the analyzed period. It leads to the complementary rationale between mandatory disclosure and the voluntary disclosure. Originality/value – The study presents a new metric for measuring the voluntary disclosure level, with the potential to understand the nature of the relationship between this and the mandatory disclosure. In the Brazilian capital market context, governed by the stakeholder model, convergence to International Financial Reporting Standards induced an increase on voluntary disclosure quality.